Rally and recover: Physiological demands between tennis drills - Glenn Björklund; Mikael Swarén; Fredrik Johansson (PLoS ONE, 2026)
This study examined physiological recovery between repeated tennis drills in elite adolescent tennis players. Ten tennis players (5 males, 5 females; age 17 ± 2 years) underwent treadmill testing to establish maximal physiological characteristics. Several days later participants completed three standardized on-court tennis drills with fixed rest intervals, during which physiological parameters were monitored. A one-way repeated-measures ANOVA was used to compare physiological responses across the three drills. V ˙ O 2max utilization stayed above 75% in all drills, peaking during the first drill (p = 0.003). During recovery, V ˙ O 2max utilization decreased from 58 ± 8% in the first recovery to 50 ± 9% (p = 0.018) and 47 ± 12% (p = 0.022) in the second and third recovery, respectively. The respiratory exchange ratio (RER) stayed below 1.0 during drills, while increasing during recovery periods, (1.07 ± 0.08, 1.00 ± 0.01, 1.04 ± 0.05; p = 0.014). Ventilatory equivalents for oxygen ( V ˙ E / V ˙ O 2 ) were stable (p = 0.054), while those for carbon dioxide ( V ˙ E / V ˙ CO 2 ) increased progressively for each recovery period (29.5 ± 3.6, 31.5 ± 3.8, 32.3 ± 4.3; p < 0.001). Blood lactate concentration differed significantly across recovery periods (p = 0.035) with the lowest value in recovery period two (5.9 ± 2.0, 4.9 ± 1.9 and 5.6 ± 2.0 mmol·l -1 ). These findings highlight a sustained metabolic demand extending into the recovery phase during standardized tennis drills, characterized by substantial V ˙ O 2max utilization and elevated respiratory compensation. This suggests a significant anaerobic contribution and underscores the intensity of the physiological load imposed even after exercise cessation.